Deteksi Buah Menggunakan Supervised Learning dan Ekstraksi Fitur untuk Pemeriksa Harga - Kristiawan Kristiawan; Deon Diamanta Somali; Try Atmaja Linggan jaya; Andreas Widjaja (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
The role of technology in the business world is growing over time. The development of technology, making machines step by step is able to replace the work done by humans. The industrial revolution is a clear example of such technologial development and its use in our daily life. in the fourth industrial revolution that we face today, IOT technology provides the ability of the five senses and think like humans to machines. Over time, human work will be replaced by such technology which provides efficiency like never before. One technology that can provide efficiency is computer vision. In retail context, computer vision can help humans to recognize fruits in supermarkets so that it will help customers do self-service, without having to ask the clerk in the fresh section of the supermarket so that supermarkets can be more efficient and customers can be served better and faster. Computer Vision and machine learning can help retail companies provide self service price checkers for fruit products in supermarkets.